The Impact of Telecommunications Infrastructure, Fintech, and E-Commerce on Economic Growth in Indonesia - Irawan, Hery; Yunani, Ahmad; Rahmini, Noor (Global Writing Academica Researching & Publishing, 2025)
This study aims to investigate how the development of telecommunications infrastructure, fintech, and e-commerce influences economic growth in Indonesia. It employs a quantitative approach using secondary data and time series analysis from 2020 to 2023. The telecommunications infrastructure is represented by fixed broadband and mobile cellular subscriptions, while the fintech aspect is evaluated through the value of transactions in fintech, and e-commerce is assessed based on its transaction values. The findings reveal a significant positive correlation, both simultaneously and individually, among telecommunications infrastructure, fintech, and e-commerce in relation to economic growth in Indonesia.